A Description of Some Key Provisions of Canada's New Civil Service Act - Best, J.C. (Relations industrielles / Industrial Relations, 1962)
SummaryThe Civil Service Act, passed in 1918, had never been substantially modified for the 43 years following its adoption. In 1957 however the Government asked the Civil Service Commission to review personnel procedure in the Government Service and to prepare a report. The report produced was entitled Personnal Administration in the Public Service.The following article is an analysis of Bill C-71, which resulted from the Commission's report and from the work of a Special Committee of the House established in 1961.